Pelatihan Pembuatan Desain UI/UX Website UMKM Profile Labscarpe dengan Aplikasi Figma: Pelatihan Desain UI/UX Website UMKM - Haida Dafitri; Erwin Panggabean; Nur Wulan; Abdul Jabbar Lubis; Sumi Khairani; Ade Putri Humaira (Cv. Utility Project Solution, 2023)
The UI/UX (User Interface/User Experience) design is a design carried out to improve the branding of an online store to get a lot of attention from the public so that it can get a bigger share. UI/UX is one of the technological developments that can take advantage of digital means to introduce a product to be offered to customers. This research is intended to help improve the branding of a store, and to find out the performance of the website after using the UI/UX. It is hoped that the UI/UX design on the Lab.Scarpe website can improve the branding of the website and make it easier for users/customers to transact on the website.